2009
DOI: 10.1128/jcm.02397-08
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Infection Caused by Macrophomina phaseolina in a Child with Acute Myeloid Leukemia

Abstract: We report a case of Macrophomina phaseolina skin infection in an immunocompromised child with acute myeloid leukemia, which was treated successfully with posaconazole without recurrence after a hematopoietic stem cell transplant. The fungus was identified by DNA sequencing using both the internal transcribed spacer and D1/D2 region of the 28S ribosomal DNA gene. CASE REPORTA 6-year-old Caucasian girl was diagnosed with acute myeloid leukemia carrying the t(11;19) translocation. She underwent a matched, unrelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 13 publications
(11 reference statements)
0
21
0
Order By: Relevance
“…32 Penetrating trauma remains the major cause of primary cutaneous zygomycosis (Table 2). [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Other causes reported include elasticized bandages and wound dressings, 55 burns, 56 motor vehicle collision, 57 intravenous access, 58 and dog bite. 59 Our case report of primary cutaneous mucormycosis after a cat bite is a rare finding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32 Penetrating trauma remains the major cause of primary cutaneous zygomycosis (Table 2). [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Other causes reported include elasticized bandages and wound dressings, 55 burns, 56 motor vehicle collision, 57 intravenous access, 58 and dog bite. 59 Our case report of primary cutaneous mucormycosis after a cat bite is a rare finding.…”
Section: Discussionmentioning
confidence: 99%
“…66 The higher overall mortality rate of 29.4% seen in the review of the literature was observed more frequently in patients with neutropenia (60.0%) and without surgical intervention (73.3%), and the survival rate was higher (35.3%) for cases utilizing both antifungal and surgical interventions. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The antifungal agent with the highest survival rate was amphotericin B and its formulations (58.8%). [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…phaseolina has shown to be comparatively a hard pathogen to control, and cultural, chemical or biological disease management strategies have failed to provide expected results (Abdel-Kader et al, 2010). So far, no registered fungicide has become available to fight M. phaseolina (Srinivasan et al, 2009), although some fungicides such as quintozene (PCNB) and captan have been used against this pathogen to some extent (Frison et al, 1990;Dubey et al, 2012). However, the plead for sustainable agriculture in an eco-friendly manner cannot be sustained with such health hazard chemicals (Oruc, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, strains that can infect plants and humans have been interestingly reported. Similarly, it is possible that it could spread widely, causing unpredictable losses to every living being (Srinivasan et al, 2009). …”
Section: Introductionmentioning
confidence: 99%